Baat as bio-etiek sonder grense: 'n gereformeerde etiese beoordeling van Artikel 4 van die Universele deklarasie vir bio-etiek en menseregte van UNESCO - R. Rheeder (Acta Theologica)
Article 4 of the UNESCO Declaration of Bioethics and Human Rights (2005) is explained as being an ethical principle and right aimed at the health environment. Benefit is defined as good deeds towards people within the medical environment and is accepted as part of universal ethics. This principle means that the person on the one hand has a right to benefit, while on the other hand has the duty to show benefit. To display benefit to mankind is to confirm the dignity of man. From a Christian perspective, the right and ethical principle of benefit is grounded in the creation, re-creation and eschatology. Man as the image of God - as a changed man in Christ - is led by the Spirit to show benefit as love to all people within the health environment.